Colonic pseudo-obstruction in a patient with Sheehan's syndrome. Issue 8 (21st August 2019) - Kaur, Navneet; Schubart, Ulrich; Mandl, Adel
Abstract : A 56-year-old woman with a history of hypothyroidism and chronic constipation presented with an acute abdomen due to colonic pseudo-obstruction. Thyroid function tests were consistent with central hypothyroidism prompting intravenous administration of stress-dose glucocorticoids and levothyroxine. The patient then underwent emergency exploratory laparotomy with sigmoid resection and end-colostomy. The postoperative endocrine evaluation revealed that the patient had panhypopituitarism due to Sheehan's syndrome (SS). The diagnosis had been missed by physicians who had been treating her for several years for presumed primary hypothyroidism with a low dose of levothyroxine, aimed at normalising a minimally elevated thyroid-stimulating hormone (TSH) level. This is the second reported case of SS presenting with colonic pseudo-obstruction and it illustrates the potential danger of relying on measurement of TSH alone in the evaluation and treatment of thyroid dysfunction.